Acute lower limb ischemia syndrome, due to femoral iliac dissecting intraparietal arterial hematoma - Larghero Ibarz, Pedro; Scarsi, R S; Negrín, G H (Cirugía del Uruguay, 2020)
Presented at session 26th March 1958